Film, music and induced mixed-emotion - Rooyen, Suzanne van (2011)
This Master's Thesis examines the relationship between film, music and induced mixed-emotion with particular focus on the effect of semantic congruency and musical background on emotion ratings. This study provides further understanding of which emotions are felt during film watching and provide an answer to whether or not there is a difference between musicians' and non-musicians' emotional reactions. A brief overview of emotion research conducted with audio and visual stimuli, as well as in film, is provided. The discussion includes the following topics: visual primacy, semantic congruency and cognitivst/emotivist theory. The difference between musicians and non-musicians as supported by various research is also covered. The various models used to measure induced emotion in music studies are discussed and adaptations for new techniques are suggested. This study reports the details of the experiment conducted with 24 university students. Participants were asked to rate how they felt in response to a variety of 30 second film excerpts (expressing either happiness or sadness) presented simultaneously with a film music excerpt chosen to express either happiness or sadness in two conditions: congruent (eg., happy visuals with happy music) and non-congruent (eg. happy visuals with sad music). Participants responded using a Likert-type scale to rate emotions listed in an extended GEMS-9 model. The analysis focused on the correlation between semantic congruency and emotion ratings as well as how, if at all, the musical background of participants affected their emotion ratings. Informal interviews conducted with participants also provided insight into some of the problems associated with emotion models dependent on verbal labels. Results show that while semantic congruency does have a significant effect on certain emotions, musical background has little to no effect on the emotional responses of participants. Results suggest that other traits such as music/film preference and familiarity with the material, cognitive styles and even nationality may prove to have a greater effect on induced mixed-emotion ratings. Although not conclusive, this study provides numerous avenues for further empirical research in the field of film and music. This study also suggests new and, or improved methods of measurement for future studies.